Potential application on preparation for bio-fertilizer using Bacillus velezensis strains isolated from various regions in Vietnam - Trung, Trịnh Thành; Vân, Đinh Thị Tuyết; Liên, Nguyễn Phương; Lương, Đào Thị; Dương Văn Hợp, Dương Văn Hợp Dương Văn Hợp (Vietnam Journal of Biotechnology, 2018)
Bacillus velezensis is a species belonging to the bacterial group of B. subtilis species complex. Due to various beneficial traits to plants, the bacterium has been received considerable attention for application in disease control and crop productivity. In this study, we isolated 15 B. velezensis strains from various soils collected in regions of Hoang Lien, Cuc Phuong, Bach Ma, Chu Yang Sin and Con Dao. All of the strains demonstrated antagonistic activity against phythopathogenic fungi of Fusarium oxysporum, Sclerotium hydrophilum, Rhizoctonia solani and Phytophthora capsici and rice blight bacterium Xanthomonas oryzae. Those strains were capable of solubilizing Ca3(PO4)2 and producing plant growth hormone of indole acetic acid (IAA). Moreover, those strains produced a series of extracellular hydrolytic enzymes such as lipase, protease, amylase, CMCase, xylanase and chitinase. Analysis of genetic diversity based on rep - PCR fingerprinting technique showed that primer ERIC had greater discrimination than primer GTG5. Number of DNA banding patterns generated by primer ERIC and GTG5 were 8 and 13, respectively. Combination of DNA banding patterns of both primers showed 14 different genotypes among 15 B. velezensis strains. Using multilocus sequencing technique, genetic diversity was confirmed by a clear discrimination of strain CP 1604 and SP 1901 in two different clusters on phylogenetic tree. Due to the possession of many beneficial traits to plant growth, pesticide protection and production of many hydrolytic enzymes, the B. velezensis strains in this study have potential application on preparation of bio-fertilizer. Further investigation is needed in order to select an appropriate strain for this application.